Research on Polymer Viscous Flow Activation Energy and Non-Newtonian Index Model Based on Feature Size. (2nd May 2019) - Lou, Yan; Lei, Qunan; Wu, Gang
Abstract : The viscous flow activation energy and non-Newtonian index properties of polymer based on feature size were studied through a series of experiments on the rheological properties of amorphous polymer polymethyl methacrylate (PMMA), semi-crystalline polymer polypropylene (PP), and crystalline polymer high-density polyethylene (HDPE) using capillary die with hole diameters of φ 0.3 mm, φ 0.5 mm, φ 1.0 mm, and φ 2.0 mm. The results show that the viscous flow activation energy of PMMA decreases with the feature size under microscopic scale. And the viscous flow activation energy of PP and HDPE increases with hole diameters of the die. Under macroscopic scale, the difference in viscous flow activation energy of all polymer materials is significantly reduced with hole diameters of the die. For the non-Newtonian index of the three polymer materials, it decreases with the feature size under the microscopic scale while it increases or does not change with the feature size under the macroscopic scale. At the same time, for different high polymer materials, the viscous flow activation energy model (SVAE model) and non-Newtonian index model (SNNE model) based on feature size were established. Finally, the accuracy and effectiveness of the SVAE model and the SNNE model are verified by comparing with the traditional model and reference data. The viscous flow activation energy and non-Newtonian index values of the polymer material can be calculated conveniently and accurately.